2020
DOI: 10.21037/jtd-20-748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and surgical outcomes of type A intramural hematoma

Abstract: Background: Data on the clinical features and surgical outcomes of type A intramural hematoma (IMH) in Chinese patients are very limited. We aimed to present the surgical experiences on type A IMH in our center, and report early and late outcomes. Methods: From February 2012 to April 2018, 106 consecutive patients underwent open surgery for type A IMH at our hospital. We adopted emergent operation for patients with cardiac tamponade or other severe complications, and recommended initial medical treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…As for CPB time, the study of Yi Shi et al. suggested that the length of CPB time (>200 min) was a risk factor for stroke, 23 and the clinical study of Antonio Salsano et al. also showed that CPB time was positively correlated with postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As for CPB time, the study of Yi Shi et al. suggested that the length of CPB time (>200 min) was a risk factor for stroke, 23 and the clinical study of Antonio Salsano et al. also showed that CPB time was positively correlated with postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Renal insufficiency was considered to be associated with adverse aorta-related events in previous studies. 36 In the MT group, renal insufficiency was significantly associated with adverse aortic events, indicating that renal insufficiency plays an independent prognostic role for risk stratification. Prior studies on patients with kidney disease have reported an independent association between renal insufficiency and calcification in the aorta.…”
Section: Discussionmentioning
confidence: 93%
“…Endovascular repair seems feasible and safe with low peri-operative and long-term morbidity and mortality in experienced centers and selected cases. presence of hypertension (>80%), which is poorly controlled (40%) or untreated (30%) [12,13]. Smoking is also detected within the most common comorbidities (40%) [12,13].…”
Section: Key Pointsmentioning
confidence: 99%
“…presence of hypertension (>80%), which is poorly controlled (40%) or untreated (30%) [12,13]. Smoking is also detected within the most common comorbidities (40%) [12,13]. Half of patients will present to the hospital within the first 24 h after symptoms' onset [12].…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation